Hello . . . Are You Still There? An Empirical Analysis How Market Structure Affects Quality of Mobile Networks - Nicolas Wellmann (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
For the ongoing and upcoming auctioning of 5G spectrum an important question is, what drives network quality in mobile markets? When comparing the provided mobile network quality between various EU countries considerable differences between these markets become apparent, which cannot be solely explained by financial and geographic factors. Recent findings in the literature suggest a negative effect of (price) competition on investments in mobile networks. To the best of our knowledge this is the first academic paper to provide a detailed analysis of how different characteristics of the market structure affect mobile network quality. In total, we consider 500 million measurements of the mobile network quality of 48 mobile network operators (MNO) from 14 European countries between 2011 and 2016. Our results indicate that a reduction in market players may actually increase mobile network quality, thus supporting the findings in the recent literature. Further, we observe a significantly higher mobile network quality for late entrants in the market, underlining how outcomes from spectrum auctions may alter competition in the mobile market.
Keywords: L96; 330; mobile telecommunication; market structure; network quality; investment; competition policy; regulation; antitrust